Organic strategies for management of Rhizoctonia leaf blight of Amaranth - M.S. SHEELA; N. DILNA, SALLY K MATHEW, RESHMY VIJAYARAGHAVAN* (Indian Phytopathology, 2016)
Leaf blight of Amaranth caused by Rhizoctonia solani was found very serious in Kerala especially during the monsoon and take a heavy toll of the crop every year. Being a leafy vegetable, an experiment was carried out for two consecutive years to study the effect of organic treatments in the management of the disease. A total of eight treatments were laid out where four applications of various treatments were given at 14 days intervals on symptom appearance and per cent disease severity was recorded 10 days after every application. Observations revealed that among the different organic treatments, cowdung slurry supernatant (2%) + P. fluorescens (2%) and turmeric soda mixture were found to be the best in reducing disease severity. Also reduction in disease severity was observed with subsequent applications, showing the effectiveness of different treatments on leaf blight management.